From the preacher's heart - M'Cheyne, Robert Murray, 1813-1843 (Christian Focus, 1993)
McCheyne's sermons are sought after because today passion in preaching is often equated with falsity. They bring the ring of Biblical authenticity, of a pastor's love for those to whom he is speaking. Here he looks at 10 virgins, the family of Bethany (Mary, Martha and Lazarus), the Good Shepherd and the town of Capernaum.